Simulation of management strategies from the DSSAT model to increase the yields of a corn cultivar - Rodríguez, O.; Florido, R.; Hernández, Naivy; Soto, F.; Jeréz, E. I.; González, Déborah; Vázquez, J. R. (Cuban Journal of Agricultural Science, 2021)
Crop simulation models based on physiological processes are valuable tools for simulating crop production, estimating agronomic efficiency, and developing optimal management practices for sustainable agriculture. The objectives of this study were to calibrate the DSSAT model for the P-7928 corn cultivar and explore management strategies to improve crop production, which included sowing density, fertilization levels and edaphoclimatic conditions. The DSSAT model showed excellent performance. The simulated yields were related to those observed, and showed a Willmott index of 0.96. The square root of the mean square of the normalized error behaved with an acceptable value of 28 % and R2 of 0.985, which shows the good fit of model and shows that it can be used to simulate the crop yield and its physiological components under Cuba conditions. The simulations performed show higher yield, when combining the sowing of 7 plants m-2 and a nitrogen fertilization of 150 kg ha-1. The comparative study of the yields in different edaphoclimatic conditions shows the influence of the latter on the crop response. Key words: calibration, crop simulation models, yield, corn